Rancang Bangun Prototipe Pengisian Air Expansion Tank Berbasis IoT - I Gede Yoga Adi Wira Nata; Agus Dwi Santoso; Ardhiana Puspitacandri (Jurnal Kendali Teknik dan Sains, 2025)
The shipping industry faces challenges in reducing environmental impact and increasing operational efficiency. Among them are the expansion tanks on ship engines which play an important role in maintaining the pressure and water quality of the engine cooling system, which is still run manually on some ships. This can result in the risk of engine damage due to overheating or unstable pressure. Manual water filling that requires crew supervision can cause operational instability. This research designed a prototype of an automatic water filling system for expansion tanks, using microcontroller-based automation technology and an Internet of things system to make monitoring easier. This system aims to increase efficiency and reduce the risk of engine damage, thereby supporting the sustainability of ship operations in the future. In the trials that have been carried out, this tool is able to operate the expansion tank filling automatically and efficiently. The distance sensor used has high accuracy with a largest error of 1.6%, and an average error of 0.01%. Integration with the Internet of Things system can run well and reliably with 100% success and latency of 0.5 – 1 second. The system's overall success rate is 80%. So the system can be used in real working conditions